The Aristotelian Conception of Natural Law and Its Reception in Early Protestant Commentaries on the Nicomachean Ethics - Svensson Manfred (Perichoresis: The Theological Journal of Emanuel University, 2022)
The Protestant reception both of Aristotle and of the concept of natural law have been the object of renewed attention. The present article aims at a cross-fertilization of these two recoveries: did a specifically Aristotelian approach to natural law (among other important sources) play a significant role in classical Protestant thought? The article answers this question by means of a review of the Protestant commentaries on Aristotle’s natural law-passage in Nicomachean Ethics V, 7. Reformation and post-Reformation scholars sometimes offered original readings of this text, but above all they cultivated the various approaches to the passage that had been developed during the medieval period.